An emic perspective on academic writing difficulties among international graduate students in Malaysia - Manjet Kaur Mehar Singh, (Penerbit Universiti Kebangsaan Malaysia, 2016)
The number of international graduate students choosing Malaysia as their destination of study is increasing. These students arrive to Malaysian shores with diverse academic, cultural and linguistic background with the intention of upgrading their academic qualification especially at graduate level. The students are confronted with a mismatch between the literacy practices in their native country and at graduate level currently. This leads to challenges in adapting to the current academic writing practices at graduate level. Academic writing is a productive skill that is pivotal to ensure academic success. However, students for whom English is a foreign language struggle in writing various sections of academic work at graduate level such as the methodology and discussion sections. This qualitative study focuses on academic writing difficulties faced by the non-native English speaking international graduate students while pursuing their Master’s degree at a public university in Malaysia. Focus group interview was used on 70 international graduate students from taught Master programs to elicit qualitative data. The main objective of the focus group interviews was to analyze how these students negotiate academic writing from an emic perspective. Through this approach, the students were able to share their own experiences of struggling with academic writing practices in higher education. The findings indicate that non-native English speaking international graduate students faced difficulties coping with academic writing especially in English as a medium of instruction setting. This study highlights the need of host institutions in providing academic support to improve the most crucial literacy skill that contributes to academic success at graduate level.